Zafar, so good: middle-class students, school habitus and secondary schooling in the city of Buenos Aires (Argentina) - Meo, Analía Inés (2011)
This article examines how students from the loser sections of the middle class dealt with the game of secondary schooling in a good state school in the city of Buenos Aires (Argentina). It engages with Bourdieus theory of social practice and, in particular, with its concepts of game, habitus and cultural capital. It argues that middle-class students embody a school habitus, which I call zafar. Zafar (a Spanish slang word) refers to students dispositions, practices and strategies towards social and educational demands of teachers and their school. Zafar propels middle-class students to be just good enough students, and promote an instrumental approach to schooling and learning. Although this paper offers an account within which the reproduction of relative educational advantage of a group of middle-class students takes place, it also poses questions about their future educational and occupational opportunities.